1997
DOI: 10.2466/pr0.1997.80.2.419
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Stereotypes and Perceptions of Competence and Qualifications

Abstract: This study investigated differences between men and women in their use of sexual stereotypes when evaluating recent hirees. Participants (33 Euro-American undergraduate women and 45 Euro-American undergraduate men) read a job announcement for Personnel Analyst and a completed employment application form (with a picture of the applicant attached). They then completed a questionnaire, indicating their perceptions of the applicant's competence, qualifications, and status on other job-related characteristics. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In an experiment that had women perform assessment center tasks, Halpert, Wilson, and Hickman (1993) found that performance evaluations were consistently lower when the employee was pregnant, and Heilman and Okimoto (2008) found a bias against women identified as being parents who were applying for promotions to traditionally male positions. In a study of hiring decisions, Snipes, Oswald, and Cavdil (1998) found that perceptions of applicants' future job performance were generally less favorable toward female applicants (see also, Lee, Castella, & McCluney, 1997). Powell, Butterfield, and Parent (2002) compared two studies 13 years apart and found that although managerial stereotypes now place less emphasis on masculine characteristics, a good manager is still seen as being predominantly masculine (see also, Brenner, Tomkiewicz, & Schein, 1989;Dodge, Gilroy, & Fenzel, 1995;Gerdes & Kelman, 1981;Heilman & Okimoto, 2007;Lyness & Heilman, 2006;Powell & Butterfield, 1989;Ruble, Cohen, & Ruble, 1984).…”
Section: Sex Stereotyping and Sex Discriminationmentioning
confidence: 99%
“…In an experiment that had women perform assessment center tasks, Halpert, Wilson, and Hickman (1993) found that performance evaluations were consistently lower when the employee was pregnant, and Heilman and Okimoto (2008) found a bias against women identified as being parents who were applying for promotions to traditionally male positions. In a study of hiring decisions, Snipes, Oswald, and Cavdil (1998) found that perceptions of applicants' future job performance were generally less favorable toward female applicants (see also, Lee, Castella, & McCluney, 1997). Powell, Butterfield, and Parent (2002) compared two studies 13 years apart and found that although managerial stereotypes now place less emphasis on masculine characteristics, a good manager is still seen as being predominantly masculine (see also, Brenner, Tomkiewicz, & Schein, 1989;Dodge, Gilroy, & Fenzel, 1995;Gerdes & Kelman, 1981;Heilman & Okimoto, 2007;Lyness & Heilman, 2006;Powell & Butterfield, 1989;Ruble, Cohen, & Ruble, 1984).…”
Section: Sex Stereotyping and Sex Discriminationmentioning
confidence: 99%